Mapping Research on Business Model Transformation Strategies as a Response to Digital Disruption to Achieve Competitive Advantage - Erika Dwi Lestari; Lina Auliana; Ratih Purbasari (Green Publisher Indonesia, 2026)
Rapid advancements in digital technologies have transformed the business environment, requiring organizations to rethink their business models to remain competitive. Digital disruption driven by technologies such as artificial intelligence (AI), big data, and the Internet of Things (IoT) has reshaped how firms create and capture value. However, existing studies on digital disruption, business model transformation, and competitive advantage remain fragmented, limiting a comprehensive understanding of research trends in this field. This study presents a systematic mapping study (SMS) and bibliometric analysis using VOSviewer to identify the research landscape regarding business model transformation strategies in response to digital disruption in an effort to achieve competitive advantage. Of the 295 initial articles identified in Scopus, 33 were selected as the most relevant and analyzed for intellectual structure, publication trends, geographic distribution, and subject area focus. The results of the keyword co-occurrence analysis show that “digital transformation” is a central concept connected to “business model,” “competitive advantage,” “AI,” “strategic management,” “value creation,” “innovation,” and “performance.” This research topic has experienced a surge in publications since 2022. This increase reflects growing urgency and academic attention, as well as the evolution of research from the basic concept of digitalization to the role of AI and performance measurement. This research topic is widely studied by developed countries such as Germany. It is also interdisciplinary and is widely examined within the subject areas of Business, Management, and Accounting.